Creative Reception in Urban Space, or the Art of Listening - Tausig, Benjamin (Journal of Urban Culture Research, 2014)
On January 15, 2011, a group of twenty Bangkok residents embarked on a guided soundwalk through parts of their city.The walk was designed as both instructional and experimental in ways that facilitated new and creative engagements between listener and place. In the middle of the walk, following a brief but serious medical emergency, it also became an exercise in responsive action, and offered the group an opportunity to reflect on the fundamental role of unpredictability in sensory experience. This article describes the planning strategies that went into developing the soundwalk, and summarizes the challenges and successes of the event as it occurred in practice. Finally, participant feedback and general recommendations for soundwalk designers are provided in the last two sections.